Perceptions of risk and influences of choice in pregnant women with obesity. An evidence synthesis of qualitative research. - Sophie Relph; Melissa Ong; Matias C Vieira; Dharmintra Pasupathy; Jane Sandall (PLoS ONE, 2020)
Background Between 7-35% of the maternity population are obese in high income countries and 1-40% in lower or middle-income countries. Women with obesity are traditionally limited by the choices available to them during pregnancy and birth because of the higher risk of complications. This evidence synthesis set out to summarise how women with obesity's perceptions of pregnancy and birth risk influence the care choices that they make. Methods A search of medical and health databases for qualitative studies written in the English language, published Jan 1993-April 2019 and reporting on pregnant women with obesity's perception of risk and influence of pregnancy and birth choices. Data was extracted by two reviewers onto a questions framework and then analysed using a thematic synthesis technique. Confidence in the qualitative findings was assessed using GRADE-CERQual. Results 23 full texts were included. The common themes on perception of risk were: 'Self-blame arising from others' stereotyped beliefs ', 'Normalisation', 'Lack of preparation', 'Fearful acceptance and inevitability' and 'Baby prioritised over mother'. For influence of choices, the themes were: 'External influences from personal stresses', 'Restrictive guidelines', 'Relationship with healthcare professional' and 'Perception of Risk'. Conclusions Evidence on what influences women with obesity's pregnancy choices is limited. Further research is needed on the best methods to discuss the risks of pregnancy and birth for women with obesity in a sensitive and acceptable manner and to identify the key influences when women with obesity make choices antenatally and for birth planning.